1987
DOI: 10.3109/02844318709086451
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin Adhesive: Its Use in Selected Skin Grafting

Abstract: The use of a fibrin adhesive to ensure the fixation of skin grafts in difficult situations was evaluated in 27 patients. Fibrin adhesive offers a fast and safe alternative to conventional methods, especially when dealing with concavities or other surfaces where it is impossible to obtain adequate fixation and prevent graft slippage. This type of adhesive has been used before, but too rapid fibrinolysis and a low concentration of fibrinogen made the method of little practical use. The method has been considerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
5

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 2 publications
0
16
0
5
Order By: Relevance
“…[18][19][20][21][22] Use of fibrin glue has been showed to be effective in skin transplants. [6][7][8][9]23 However, periocular area poses a challenge during skin grafting due to constant movements of eyelid. There is a paucity of material on use of fibrin glue in eyelid reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] Use of fibrin glue has been showed to be effective in skin transplants. [6][7][8][9]23 However, periocular area poses a challenge during skin grafting due to constant movements of eyelid. There is a paucity of material on use of fibrin glue in eyelid reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…FA'in etkileri; hemostazı sağlaması, dokuda adezyon (yapışma) oluşturması ve yara iyileşmesine yardımcı olması şeklinde özetlenebilir (Seelich, 1982 (Lilius, 1987). Mellin (1986) yaptığı çalışmada, FA'in kapatıcı özelliği nedeniyle acil göz cerrahisinde kullanılmasını önermektedir.…”
Section: Introductionunclassified
“…Literatür verilerde, hastanın kendi serumu İle hazırlanmadan, sadece FA kiti komponentleri kullanılarak yapılan çalışmalarda, viral enfeksiyon ya da allerjik reaksiyon komplikasyonu bildirilmemiştir (Seelich, 1982;Buschmann, 1986a;Buschmann, 1986b;Flacinelli ve ark. 1986;Mellin, 1986;Steinkogler, 1986;Lilius, 1987 FA'in, pıhtılaşma reaksiyonuna benzer bir reaksiyonla çalışması nedeniyle hemostatik etkisinin bulunduğu bildirilmektedir (Seelich, 1982;Lilius, 1987;Zauberman 1988 (Seelich, 1982;Mellin, 1986;Laqoutte ve ark., 1989 …”
Section: Introductionunclassified
“…13 Another study showed that fibrin sealant provided mechanical strength in the first days of healing, when the wound possesses little independent mechanical strength. 3 Fibrin sealants have also been found to greatly decrease operating time 8,14 and have been reported to improve wound healing and the final scar. 1,6 The elimination of suture removal could be a great advantage, especially when working with children.…”
Section: Introductionmentioning
confidence: 99%